(untitled) (American Journal of Islam and Society, 2012)
In contemporary times, the relationship between Islam and democracy – democracy and its Islamic heritage and the process of democratization in Muslim societies, and other related themes – is a hotly debated and discussed topic. Throughout the Muslim world – from South, Southeast and Central Asia to Middle East and North Africa – Muslim thinkers have undertaken the effort of working within and cooperating with existing political regimes and authorities ‒ from republics, monarchies and authoritarian dictatorships to pluralistic and relativity homogeneous societies. With the desire for democratization, along with the continuing resurgence of Islam in a dynamic global context, the demand and desire for democracy is widespread. Two of the major developments in the final decades of the twentieth century to present are “religious resurgence” and “democratization.” The debate over democracy and democratization in the Muslim societies, its definition and fundamentals, has continued for a long time, but, as it has acquired an impetus in recent years, and this debate has become highly intensified. The Muslim world at present is the most diverse in the forms of the political systems it employs. It has traditional and constitutional monarchies, dictatorships, Islamic republics, and secular and some liberal democracies ‒ and due to the diverse interpretations of its laws and sources of law, Islam possesses intellectual and ideological resources that can provide justification for a wide range of governing models from monarchy to democracy ...